2005
DOI: 10.2174/1568016054368223
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of 3-Hydroxy-3-methylglutaryl-coenzyme A Reductase Inhibitors: Candidate Mechanisms for Anti-Lipid Deposition in Blood Vessels

Abstract: The 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors (statins) are considered first-line therapeutic agents for the prevention of coronary heart disease and atherosclerotic disorders related to hypercholesterolemia. Statins inhibit lipid deposition in the aortic endothelium. Although it has been accepted that the statins are potent inhibitors of cholesterol biosynthesis in the liver and that they lower circulating cholesterol levels, several cholesterol-independent (pleiotropic) effects have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…There are, however, additional effects of statins that appear to be independent of LDL-C. Best described is the well-known effect of nitric oxide (NO) on the inhibition of platelet aggregation. Statins cause an upregulation of endothelial NO synthase, leading to increased NO at the vascular endothelium and a subsequent vascular dilation and diminution of platelet adhesion [12,13]. This appears to be an effect independent of lipid modification.…”
Section: Thrombosismentioning
confidence: 96%
See 2 more Smart Citations
“…There are, however, additional effects of statins that appear to be independent of LDL-C. Best described is the well-known effect of nitric oxide (NO) on the inhibition of platelet aggregation. Statins cause an upregulation of endothelial NO synthase, leading to increased NO at the vascular endothelium and a subsequent vascular dilation and diminution of platelet adhesion [12,13]. This appears to be an effect independent of lipid modification.…”
Section: Thrombosismentioning
confidence: 96%
“…This has been studied in in vitro and animal models but remains difficult to measure in clinical studies [12]. Clinical trials have shown, however, a significant reduction in fibrinogen levels with long-term statin therapy, increased levels of tissue-type plasminogen activator, and a reduction in the phospholipid content of platelet membranes [15,16].…”
Section: Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…While the effects of statins on plasma lipid levels are well described, the actual mechanisms by which these and other effects are obtained are not always clear (2). Statins have pleiotropic effects at the physiological level (e.g., depression, insomnia, neuropathy, antiinflammatory, and antiatherogenic effects) as well as at the cellular (e.g., interference with lysosomal functions) and biochemical levels (e.g., reduced isoprenylation of proteins and inhibition of GTPases) (3)(4)(5)(6). Furthermore, statins are increasingly being considered as anti-cancer drugs because of their effects on the RAS superfamily of GTPases (1) and have recently proven protective against heart failure in patients where cholesterol levels are not elevated (7).…”
mentioning
confidence: 99%
“…Moreover, both dipyridamole [32] and cilostazole [50] augment the infarct-size limiting effect of low-dose ATV by augmenting myocardial levels of adenosine. In addition to their protective effects against ischemia-reperfusion injury, Akt and eNOS activation have central roles in mediating other pleiotropic effects of statins, such as vasodilation, antiinflammatory effects, anti-platelet effects, anti-atherosclerosis effects, mobilization of endothelial progenitor cells and neovascularization [51][52][53]. Thus, heavy consumption of CC may deprive patients from these potentially important non-lipid lowering effects of statins.…”
Section: Discussionmentioning
confidence: 99%